0235 Framework to match exposure and health outcomes to build health management system for construction workers in korea. (21st August 2017) - Choi, Hyunwoo; Kang, Dongmug; Kim, Jongeun
Abstract : Background: Majority of construction workers are daily workers who move into many places frequently. Because of this characteristic of construction workers, it is difficult to monitor their exposure status and manage health including periodic health check-up. Therefore, there is a need to establish a health management system, which includes method to assess exposure and health status. Methods: Identification data for individual will be gathered based on the database of the Construction Workers Mutual Aid Association(5 million registered) and the Korean Construction Workers Union database(7000 registered). Those databases have present job title and duration. Since the database do not have exact past exposure data, questionnaire using mobile and web survey will be considered. Main interest of exposures are asbestos and silica using Korean JEM. Major health outcomes will be asbestosis, chronic obstructive pulmonary disease, lung cancer. In addition, other diseases including musculo-skeletal disorders can be the other outcomes. Health outcomes will be recognised by the data of the National Health Insurance data by matching social security numbers whose were acquired from the exposure database. Results: This is in the beginning of the study. The detailed study design will be formed in the first year(2017). In 2018, preliminary analysis with matching of JEM and health outcomes in individual level will be given. Health management system and prospective cohort follow-up will be conducted after 2019. In the presentation, detailed study design, databases regarding construction workers in Korea will be shown.